Development of Motion Sensor Device for Athlete Posture Assessment During Ergometer Rowing Machine Training - Rahman, Ahmad Fikri; Bakar, Lilywati Binti Bakar (Progress in Engineering Application and Technology, 2023)
This project aims to use electronic components for indoor sports. Electronic components include sensors and microcontrollers. The sport of rowing was chosen to make this project a success because rowers are very active in training at the residential college. Almost every evening we can see rowing athletes doing rowing machine exercises to strengthen themselves with rowing. As an experienced athlete, it is no problem to do this exercise. Beginner athletes have difficulty starting the training because they do not know the correct body posture when doing this rowing exercise. This project is to examine and evaluate the athlete’s body posture while doing this exercise. There are several types of techniques in this rowing exercise that will be an experiment to make the sensors able to detect the posture of the athlete’s body. This project works by using sensors such as IR and Ultrasonic sensors. This sensor works to detect the presence of the athlete’s body during training. The controller used is Node MCU and Arduino Nano and the LED serves as an indicator to know whether their body posture is good enough or not. The athlete just needs to sit down and pull the handle while straightening the legs. The correct body structure is that the athlete needs to straighten the body while bringing the hands close to the chest and straightening the legs.